Molecular variability of cassava Bemisia tabaci and its effects on the spread of cassava mosaic begomoviruses in East Africa - Mugerwa, Habibu (My University, 2014)
Bemisia tabaci is the vector of cassava mosaic begomoviruses and cassava brown streak viruses which are main production constraints to cassava in sub-Saharan Africa. Current vector dynamics involved in the spread of both viruses in the region was established through comparison of the mitochondria cytochrome oxidase I DNA. Two distinct species were obtained: sub-Saharan Africa clade 1 (SSA1), comprising of two sub-clades (I & II), and a South West Indian Ocean Islands (SWIO) species. SSA1 sub-clade I whiteflies were widely distributed in East Africa. SSA1 sub-clade II whiteflies predominated the coast regions of Kenya, southern & coast regions of Tanzania and widespread in Uganda. SWIO whiteflies occurred in the coastal region of Kenya. This study also revealed that SSA1 sub-clade I haplotypes performed significantly better than SSA1 sub-clade II haplotypes with respect to mean number of eggs laid, developing instars and hatched adults on healthy, African cassava mosaic virus-[Tanzania:2001 ] and East African cassava mosaic Kenya virus-infected plants. There was no boost in whitefly numbers by the CMB-infected plants. The fecundity and development differences observed between SSA1 sub-clade I and II haplotypes have major epidemiology implications on the CMGs in the region
Keywords: Cassava - Research.; Cassava - Diseases and pests.; Cassava mosaic disease - East Africa.; Plant viruses - East Africa.